2019
DOI: 10.1186/s41702-019-0040-4
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired methicillin-resistant Staphylococcus aureus colonization in atopic dermatitis patients in Mansoura, Egypt

Abstract: Background: Atopic dermatitis (AD) patients are more frequently colonized with Staphylococcus aureus. The aim of this study is to determine the prevalence of community-acquired methicillin-resistant S. aureus (CA-MRSA) colonization in AD patients in a dermatology clinic in Mansoura, Egypt, and to assess the resistance pattern and the superantigen genes among isolated strains. Methods: Sixty AD patients were evaluated for the carriage of CA-MRSA in both lesional skin and nose. Antimicrobial susceptibility tests… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
(28 reference statements)
1
2
0
Order By: Relevance
“…A lower overall resistance rate of 6.85% was observed for ciprofloxacin. This confirms a previous report of a low resistance rate for CA-MRSA in Mansoura [ 41 ]. It seems that ciprofloxacin is not very commonly prescribed at Mansoura, and therefore, MRSA isolates are still highly sensitive to it.…”
Section: Discussionsupporting
confidence: 92%
“…A lower overall resistance rate of 6.85% was observed for ciprofloxacin. This confirms a previous report of a low resistance rate for CA-MRSA in Mansoura [ 41 ]. It seems that ciprofloxacin is not very commonly prescribed at Mansoura, and therefore, MRSA isolates are still highly sensitive to it.…”
Section: Discussionsupporting
confidence: 92%
“…In this study, MRSA isolates were found in 43.6% of AD patients in at least one of the clinical sites surveyed. Worldwide, rates of MRSA colonization in patients with AD have ranged from 16% to 57.4% [ 15 , 17 , 37 , 39 , 59 ]. For example, Ali et al (2019) [ 59 ] found MRSA isolates in 57.4% of lesioned skin and nares samples from AD patients attending clinics in Egypt.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, rates of MRSA colonization in patients with AD have ranged from 16% to 57.4% [ 15 , 17 , 37 , 39 , 59 ]. For example, Ali et al (2019) [ 59 ] found MRSA isolates in 57.4% of lesioned skin and nares samples from AD patients attending clinics in Egypt. However, the prevalence of MRSA isolates can vary between countries and even within regions of the same country.…”
Section: Discussionmentioning
confidence: 99%